The Impact of Covid-19 on Honorary Teachers in Medan City - Nadila Eka Putri; Lubis, Tasya Ayu Tandira; Yulia Rustanti; Elitaria Bestri Agustina Siregar; DINAMIKA, SORAYA GRABIELLA (Adpebi Science Series, 2022)
The purpose of this study is to analyze the impact caused by the Covid-19 pandemic, one of which is the reduction in income for honorary teachers. This study uses a quantitative method, which is carried out by distributing online questionnaires using a google form to 10 honorary teachers as respondents. This study aims to determine the impact of the Covid-19 pandemic on the income of honorary teachers and the consequences of the reduced economic income of honorary teachers in Medan, North Sumatra. From the research, it was found that 4 or 40 percent of the 10 or 100 percent of the honorary teachers who became respondents experienced a reduction in income, while 6 or 60 percent of the 10 or 100 percent of the honorary teachers who became respondents did not experience a reduction in income. Conclusion: The Covid-19 pandemic has not only had an impact on the income of honorary teachers whose economic income has decreased but also on honorary teachers whose economic income has not decreased. According to the results obtained from the Geriatric Depression Scale (GDS), the depression level of honorary teachers who experienced and did not experience a reduction in income showed that 10 or 100 percent of the honorary teachers who were respondents were affected by the level of depression where 6 out of 60 percent experienced mild depression, 3 or 30 percent were at normal levels, and 1 or 10 percent had major depression.